The Effect of Jigsaw-Type Cooperative Learning Model with a Multimodal Approach on the Creativity of Grade XI Students - Lalu Azikri Amrullah; Gunawan Gunawan; Kosim Kosim; Aris Doyan (Indonesian Publication Center, 2026)
Creativity is a crucial aspect of physics learning that is often overlooked due to the dominance of conventional learning methods. This study aims to analyze the influence of the Jigsaw cooperative learning model with a multimodal approach on the creativity of grade XI students at MA Nurul Iman. This research is a quasi-experiment using a non-equivalent control group design. The research instrument consisted of a creativity test in the form of four complex essay items that were declared valid (rxy>0,443) and reliable (r11>0.443). The results showed that the average posttest score of the experimental class (78) was higher than the control class (65.05). The Independent Sample T-test results obtained a significance value (2-tailed) of 0.002 < 0.05, so Ha was accepted. It can be concluded that the implementation of the Jigsaw model with a multimodal approach has a significant effect on students' creativity. The synergy between individual responsibility in groups and the diversity of representation modes effectively stimulates indicators of fluency, flexibility, originality, and elaboration.